Influence of the professional vocation on the academic performance of students of Veterinary Medicine and Zootechnics in a private university of Lima, Peru - Medina Sparrow, Carlos (2018)
One of the main problems that students of high school pose when concluding their studies consists in choosing wisely the profession to follow. When this decision is not taken with sufficient maturity and following the vocation, the consequent problems encompass a poor academic performance, desertion with loss of time and money, or culminate a profession without satisfaction, which leads to mediocrity and incompetence. The aim of this study was to determine if the vocation and the choice of the career of Veterinary Medicine and Zootechnics are related to the academic performance of the students of a private university in Lima, Peru. A total of 171 students were distributed into three groups according to their academic performance (high, medium and low) and their level of studies by academic semesters (initial, intermediate and final). The evaluation instrument was a survey of 36 questions covering four dimensions of professional vocation: satisfaction with the chosen profession, interest in obtaining a profession, self-confidence, and skills and abilities. It is concluded that none of the four dimensions were related to academic performance. The self-confidence dimension was statistically significant with respect to the level of studies, meaning that the higher the level reached, the greater the self-confidence.